2. Chalcothallite- a new Sulphide of Copper and Thallium from Ilímaussaq Intrusion, South Greenland. - Semenov, E. I.; Sørensen, H.; Bessmertnaja, M. S.; Novorossova, L. E. (Meddelelser om Grønland, 1967)
The new mineral chalcothallite, Cu3TlS2 was discovered in a hydrothermal ussingite vein in poikilitic sodalite syenite (naujaite) in the Ilímaussaq intrusion, South Greenland. The new mineral is associated with ussingite, analcime, sodalite, epistolite and chkalovite. The mineral forms lamellar aggregates. The colour is lead grey to iron black with metallic lustre. There are three mutually perpendicular cleavages. The specific gravity is 6.6, the hardness is 61 - 90 kg/mm2. The chemical composition is: Tl- 38.07, Cu - 40.58, Ag - 0.19, Pb - 0.13, Fe - 3.79, S -12.06, Sb - 3,93, insoluble 1.52 ; total 100.27. The d-values of the strongest lines of the x-ray powder diagram are : 3.93, 3.75, 3.49, 3.07, 2.48, 2.32, 2.19, 1.930. Like chalcocite, chalcothallite is easily subject to transformation and recrystallization. There are inclusions of native silver, chalcocite, vrbaite and avicennite (? ).